Paphlagonien: das Land, seine Herrscher und seine Götter in der Zeit des pontischen Königshauses und in der Kaiserzeit - Chiai, Gian Franco (2019)
After a synthetic reconstruction of the historical and religious development of this region, the aim of this essay is to examine the character of the gods worshiped in the Paphlagonian Poleis and in the countryside during the Hellenistic and Roman times by comparative analysis of the epigraphic and numismatic evidence. Furthermore, the notable parallels with the local rural cults of Phrygia and Lydia of the Roman period are highlight. A noteworthy peculiarity is also the use of religious epithets, derived from place-names. These epithets underline the strong relationship of the god with the territory, in which this divine being represents the main god worshiped within a rural community.